Respon Cabai Rawit (Capsicum frutescens L.) Terhadap Pupuk Organik Cair Berbahan Lindi pada Lahan Marginal - Sanjaya, Muhammad Fahyu; Alim, Nurmaranti; Suyono; Sari, Dwi Ratna; Mahendra, Yusril (Jurnal Galung Tropika, 2024)
Coastal land is identical to marginal land, namely having a low soil fertility level. Liquid organic fertilizer (LOF) made from leachate can be used to increase the availability of nutrients in the soil. This study focuses on increasing the growth and yield of cayenne pepper plants on marginal land using various doses of liquid organik fertilizer made from leachate. This study was conducted from May to September 2023. The treatment was the provision of LOF consisting of 4, namely without LOF, 20%, 40%, and 60%. The results of the study showed that the liquid organic fertilizer treatment was able to increase nutrients in the soil. Treatment without liquid organic fertilizer and 60% liquid organik fertilizer significantly affected plant height. Meanwhile, the treatment without liquid organic fertilizer and 20% liquid organic fertilizer was significant for stem diameter, number of fruits, and fruit weight of cayenne pepper plants. The 20% liquid organik fertilizer treatment is recommended to increase the growth and yield of cayenne pepper plants.